Creolage. A Bottom-Up Approach to Cultural Change in Roman Times. Issue 1 (24th November 2020) - Haeussler, Ralph; Webster, Elizabeth
Existing theories to explain socio-cultural developments in the highly interconnected Roman world have seen significant developments over the past 20 years. But are we any closer in answering three major questions: who, how, and why? In other words, we need a better understanding of the complexity of the mechanisms of social agency and multiple motivational forces that instigate socio-cultural change. Many models appear to underestimate the role of sub-elite agents in instigating change, nor do they take into account simultaneous, often contradictory societal, cultural, religious and economic developments. We are therefore advocating a bottom-up approach whereby multiple experiences, expectations, norms and social pressures shaped the individual social agents in diverse geographical settings in this emerging 'global world'. To evaluate the potential repercussions of an individual's actions and decisions, we must use modern sociological approaches that help us to understand, for example, group dynamics.